The Italian data on SARS-CoV-2 infection in transplanted patients support an organ specific immune response in liver recipients - Rendina, Maria; Barone, Michele; Lillo, Chiara; Trapani, Silvia; Masiero, Lucia; Trerotoli, Paolo; Puoti, Francesca; Lupo, Luigi Giovanni; Tandoi, Francesco; Agnes, Salvatore; Grieco, Antonio; Andorno, Enzo; et al. (Frontiers in Immunology, 2023)
Introduction: The study of immune response to SARSCoV-2 infection in different solid organ transplant settings represents an opportunity for clarifying the interplay between SARS-CoV-2 and the immune system. In our nationwide registry study from Italy, we specifically evaluated, during the first wave pandemic, i.e., in non-vaccinated patients, COVID-19 prevalence of infection, mortality, and lethality in liver transplant recipients (LTRs), using non-liver solid transplant recipients (NL-SOTRs) and the Italian general population (GP) as comparators. Methods: To compare the sex- and age-adjusted distribution of infection, mortality, and lethality in LTRs Italian GP and NL-SOTRs, we applied an indirect standardization method to determine the standardized rate. Case collection started from February 21 to June 22, 2020, using the data from the National Institute of Health and National Transplant Center, whereas the data analysis was performed on September 30, 2020, to consolidate data reporting. Results: Among the 43,983 Italian SOTRs with a functioning graft, LTRs accounted for 14,168 patients, of whom 89 were SARS-CoV-2 infected. In the 29,815 NL-SOTRs, 361 cases of SARS-CoV-2 infection were observed. The geographical distribution of the disease was highly variable across the different Italian regions. The standardized rate of infection, mortality, and lethality rates in LTRs resulted lower compared to NL-SOTRs [1.02 (95%CI 0.81-1.23) vs. 2.01 (95%CI 1.8-2.2); 1.0 (95%CI 0.5-1.5) vs. 4.5 (95%CI 3.6-5.3); 1.6 (95%CI 0.7-2.4) vs. 2.8 (95%CI 2.2-3.3), respectively] and comparable to the Italian GP. Discussion: According to the most recent studies on SOTRs and SARS-CoV-2 infection, our data strongly suggest that, in contrast to what was observed in NL-SOTRs receiving a similar immunosuppressive therapy, LTRs have the same risk of SARS-CoV-2 infection, mortality, and lethality observed in the general population. These results suggest a different immune response to SARS-CoV-2 infection in LTRS and NL-SOTRs, probably related to the ability of the grafted liver to induce immunotolerance.